Effect of Chitosan Coating with Cinnamon Oil on the Quality and Physiological Attributes of China Jujube Fruits. (30th September 2015) - Xing, Yage; Lin, Hongbin; Cao, Dong; Xu, Qinglian; Han, Wenfeng; Wang, Ranran; Che, Zhenming; Li, Xihong
Abstract : Effects of chitosan coating with cinnamon oil on the physiological attributes and preservation quality of China jujube fruits during storage at 4°C for 60 days were investigated. Results indicated that weight loss and decay of jujube fruits were significantly reduced by chitosan-oil coating during the period of 60-day storage, which also exhibited a quite beneficial effect on maintaining the sensory quality for jujube fruits. Meanwhile, the contents of vitamin C and titratable acid decreased to 3.08 mg·g −1 and 0.342% for the fruits treated by chitosan-oil coating (1.0% + 0.10%), respectively. Polyphenol oxidase, superoxide dismutase, and peroxidase activities were 13.40 U·g −1, 14.53 U·g −1, and 63.6 U·g −1 at the end of storage, respectively. The contents of total soluble phenolics and MDA were 34.51 mg·g −1 and 19.43 μ mol·g −1 for the combined coating treated samples and control fruits, respectively. These results suggested that the chitosan-oil coating might be recognized as one efficiency technology on the preservation quality of jujube fruits during the storage time.